ANALISIS PENETAPAN HARGA JUAL PERUMAHAN BERDASARKAN TARIF BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PADA PT. BANGUN KARYA SEJAHTERA - Yusuf Adi Wijaya; Wibowo Andoko; Dwi Budiadi (POLITEKNIK CAHAYA SURYA, 2018)
Selling price is an important factor for the company because it is the basis in determining the expected profit. The purpose of this study is to analyze the determination of the selling price of housing based on the tariff of Customs Acquisition of Land and Building Rights. The subject of this research is at Developer PT. Build Prosperous Work. Sources of data used are primary and secondary data, data obtained directly by conducting interviews related to the problems studied and documentation in the form of housing sales report in 2015, BPHTB rates and data on the sale of housing Puri Pagut Asri, Resident Pearl housing and Residential Cempaka Resident. The analysis technique used is descriptive qualitative that is analyzing and describing the data obtained. From the results of the analysis shows the determination of the selling price in each housing has a different price, Based on the results of the study, the authors concluded that the calculation of the determination of the selling price of housing based on tariffs of Acquisition of Land and Building Rights is in accordance with government regulations. Keywords : Determination of Sale Price of Housing, BPHTB